The effect of E-LKPD on the inquiry-flipped classroom model and self-efficacy on students' creative thinking ability - Suci Desmarani; Muhammad Rusdi; Haryanto Haryanto; Sugeng Triwahyudi (Pascasarjana Universitas Negeri Medan, 2022)
The active role of students is also very closely related to the confidence that students have in solving various problems and discovering concepts in chemical bonding material. This study aims to see the effect of the inquiry-flipped classroom model assisted by E-LKPD media on students' creative thinking abilities in chemical bonding material. The sample used was 2 classes at Al-Falah High School, Jambi City. The data collection instruments used were self-efficacy questionnaires and essay test questions. The results showed that there was an effect of E-LKPD on the inquiry-flipped classroom model on students' creative thinking abilities in chemical bonding material with a significance level of 0.027. Then students who have high self-efficacy with students who have low self-efficacy influence the ability to think creatively on chemical bonding material with a significance value of 0.04. Furthermore, there is no interaction between the E-LKPD in the inquiry-flipped classroom model and self-efficacy on students' creative thinking abilities in chemical bonding learning, which can be seen from the significance value of 0.694 > 0.05.Keywords: E-LKPD; Chemical bond; Creative thinking; Inquiry-flipped classroom; Self-efficacy